INVENTARISASI JENIS-JENIS RHODODENDRON (ERICACEAE) PADA HUTAN PEGUNUNGAN TAMAN NASIONAL LORE LINDU (TNLL) SULAWESI TENGAH - Masnawati Masnawati; Ramadhanil Pitopang; Samsurizal Suleman (Biocelebes, 2017)
A research entitled  “Inventory of Rhododendron (Ericaceae) at the Montane Forest of Lore Lindu National Park (LLNP) Central Sulawesi has been conducted from March to August 2016. The Research was located at two locations namely: path of Mt. Nokilalaki (1065-2355 m asl) and path of Mt Rorekautimbu (1699 -2070 m asl)  used survey method by using the botanical exploration methods. All Rhododendron species  were collected in sets of at least two duplicates. Plant collecting was according to the “Schweinfurth method” (Pitopang et al, 2011). Processing of the specimens was conducted at the Laboratory of Biodiversity Department of Biology, Faculty of Mathemathics and Natural Sciences Tadulako University. Identification was done in the field, in CEB, and the Herbarium Bogoriense (BO), Cibinong West Java. Vouchers were deposited in Laboratory of Biodiversity Department of Biology, Faculty of Mathemathics and Natural Sciences Tadulako University. The results showed that there were four (4) species of Rhododendron from the area of study namely Rhododendron malayanum Jack, Rhododendron quadrasianum S. Vidal var. celebicum J.J.Sm. (Nokilalaki), Rhododendron zollingeri J.J.Sm. and Rhododendron celebicum DC (Rore Kautimbu).